(untitled) (Research, Society and Development, 2020)
This study aimed to analyze the menu and the physical-structural conditions of Food and Nutrition Units (FNU) from prisions in a municipality from Piauí. The analysis of the menu offered at these institutions was carried out using the QAMP method (Qualitative Analysis of Menu Preparations) and the hygienic and sanitary conditions were carried out using the checklist adapted from RDC nº 275/2002. On the analyzed menu, the group of leafy, fatty meat and fried foods were offered daily (100%), with low weekly frequency of the same colors (28.57%) and fruits, sulfur foods, sweets, as well as frying and sweet. The two UAN penitentiaries showed a high percentage of non-conformities, in which Penitentiary B obtained the highest percentage (84.68%), being classified as very bad and Penitentiary A, as bad (63.70%). The FNU presented a menu with high weekly frequency of food groups considered harmful to the health of of the population deprived of liberty, as well as having inadequacies in most items evaluated from the physical-structural and hygienic-sanitary point of view, thus compromising the provision of safe food.